2007
DOI: 10.1002/mds.21495
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric changes of sensorimotor structures in focal dystonia

Abstract: Idiopathic cervical dystonia (CD) and benign essential blepharospasm (BEB) are the most common forms of focal dystonia. Previous autopsy and imaging studies suggested that these disorders are not accompanied by structural brain abnormalities. However, recent brain voxel-based morphometry (VBM) studies of these conditions suggest that there actually may be changes in gray matter. The objective of this stdy was to detect possible gray matter abnormalities in patients with CD and BEB using VBM and to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 26 publications
7
131
2
2
Order By: Relevance
“…6 By contrast, unlike other authors who reported a GM increase in the thalamus, caudate nucleus, and left cerebellum, 6 we found no GM volume increase in any sensorimotor network structure. We attribute the discrepancies to several factors: We studied a larger sample of patients with CD than those studied by Obermann et al 6 and Egger et al 7 ; our patients had a longer disease duration and were younger than those reported by others. 6,7 Mapping the progression of changes in GM volume with time in the same patients showed that GM volumes in the left primary sensorimotor cortex decreased further during the subsequent 5-year interval.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…6 By contrast, unlike other authors who reported a GM increase in the thalamus, caudate nucleus, and left cerebellum, 6 we found no GM volume increase in any sensorimotor network structure. We attribute the discrepancies to several factors: We studied a larger sample of patients with CD than those studied by Obermann et al 6 and Egger et al 7 ; our patients had a longer disease duration and were younger than those reported by others. 6,7 Mapping the progression of changes in GM volume with time in the same patients showed that GM volumes in the left primary sensorimotor cortex decreased further during the subsequent 5-year interval.…”
Section: Discussioncontrasting
confidence: 97%
“…We attribute the discrepancies to several factors: We studied a larger sample of patients with CD than those studied by Obermann et al 6 and Egger et al 7 ; our patients had a longer disease duration and were younger than those reported by others. 6,7 Mapping the progression of changes in GM volume with time in the same patients showed that GM volumes in the left primary sensorimotor cortex decreased further during the subsequent 5-year interval. The GM changes we found in patients with CD suggest a disease-related loss of neuronal density in the caudate, putamen, and sensorimotor cortex.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Contradictory results have been found with voxel-based morphometry. Some studies noticed increased volumes in the sensorimotor cortex (132), putamen (133), globus pallidus (134) and cerebellum (135), but other decreased volumes in the putamen (136) sensorimotor cortex (137), cerebellum and thalamus (136,137). These results must be interpreted in a phenomenological perspective since dfferent types of dystonia may yield different results.…”
Section: Neuronal Network (Imaging Data)mentioning
confidence: 99%